LOST IN SPACE. (From Abba to Zoom: A Pop Culture Encyclopedia of the Late 20th Century, 2005)
Information about the science-fiction television program "Lost in Space," is presented. The show was based on the comic books "Space Family Robinson." The show, which aired on television network CBS from 1965-68, starred Guy Williams and June Lockhart. The show was about the Robinson family who was sent by the U.S. government in 1997 to start a colony on a planet in the Alpha Centauri star system.